GAMBARAN KONSUMSI ENERGI DAN PROTEIN PADA REMAJA DI SMA MUHAMMADIYAH BATUDAA KABUPATEN GORONTALO - Nusi, Fitriani; Arbie, Fitri Yani (JOURNAL HEALTH AND NUTRITIONS, 2018)
ABSTRACT Background: Nutritional consumption greatly influences a person's nutritional status which is the main capital for an individual's health. Nutritional intake that is wrong or not in accordance with needs will cause a variety of health problems including adolescents. This study aims to determine energy and protein consumption in adolescents at Batudaa Muhamadiyah High School Gorontalo District Method: This research method is descriptive survey. The study sample was 100 adolescents at Batudaa Muhamadiyah High School, Gorontalo District by recalling energy and protein intake in adolescents for 3 days using food recall. Results: The results of the study were 93% of adolescents had less energy intake and 7% had good energy intake. There were 42% of teenagers having less protein intake, 40% of teenagers having good protein intake, and 18% having more protein intake. Conclusion: The conclusion of the study is that energy and protein consumption in adolescents at Muhammadiyah Batudaa High School in Gorontalo Regency is still categorized as less than the Nutrition Adequacy Rate. Keywords: energy, adolescents, protein ABSTRAK Latar belakang: Konsumsi gizi sangat mempengaruhi status gizi kesehatan seseorang yang merupakan modal utama bagi kesehatan individu. Asupan gizi yang salah atau tidak sesuai dengan kebutuhan akan menimbulkan berbagai masalah kesehatan termasuk pada remaja. Penelitian ini bertujuan untuk mengetahui konsumsi energi dan protein pada remaja di SMA Muhamadiyah Batudaa Kabupaten Gorontalo Metode: Metode Penelitian ini bersifat survei deskriptif. Sampel penelitian sebanyak 100 remaja di SMA Muhamadiyah Batudaa Kabupaten Gorontalo dengan merecall asupan energi dan protein pada remaja dilakukan selama 3 hari meggunakan food recall. Hasil: Hasil penelitian sebanyak 93% remaja memiliki asupan energi kurang dan 7% memiliki asupan energi baik. Terdapat 42% remaja memiliki asupan protein kurang, 40% remaja memiliki asupan protein baik, dan 18% memiliki asupan protein lebih. Kesimpulan: Kesimpulan penelitian yaitu konsumsi energi dan protein pada remaja di SMA Muhammadiyah Batudaa Kabupaten Gorontalo masih termasuk kategori kurang dari Angka Kecukupan Gizi.